DEVELOPMENT OF STUDENTS THINKING IN STUDYING A FOREIGN LANGUAGE (Pedagogy of Higher and Secondary Education, 2022)
The article deals with educational-methodical complex that promotes effective lesrning foreign language.
Keywords: thinking; professional culture; controversies; educational and methodical complex